Scaling up resource recovery of plastics in the emergent circular economy to prevent plastic pollution: Assessment of risks to health and safety in the Global South. Issue 12 (December 2022) - Cook, Ed; Velis, Costas A; Cottom, Joshua W
Over the coming decades, a large additional mass of plastic waste will become available for recycling, as efforts increase to reduce plastic pollution and facilitate a circular economy. New infrastructure will need to be developed, yet the processes and systems chosen should not result in adverse effects on human health and the environment. Here, we present a rapid review and critical semi-quantitative assessment of the potential risks posed by eight approaches to recovering value during the resource recovery phase from post-consumer plastic packaging waste collected and separated with the purported intention of recycling. The focus is on the Global South, where there are more chances that high risk processes could be run below standards of safe operation. Results indicate that under non-idealised operational conditions, mechanical reprocessing is the least impactful on the environment and therefore most appropriate for implementation in developing countries. Processes known as 'chemical recycling' are hard to assess due to lack of real-world process data. Given their lack of maturity and potential for risk to human health and the environment (handling of potentially hazardous substances under pressure and heat), it is unlikely they will make a useful addition to the circular economy in the Global South in the near future. Inevitably, increasing circular economy activity will require expansion towards targeting flexible, multi-material and multilayer products, for which mechanical recycling has well-established limitations. Our comparative risk overview indicates major barriers to changing resource recovery mode from the already dominant mechanical recycling mode towards other nascent or energetic recovery approaches.